2021
DOI: 10.3390/catal11080887
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Conversion into 5-Hydroxymethylfurfural over Niobium Oxides Supported on Natural Rubber-Derived Carbon/Silica Nanocomposite

Abstract: 5-Hydroxymethylfurfural (HMF) is one of the most important lignocellulosic biomass-derived platform molecules for production of renewable fuel additives, liquid hydrocarbon fuels, and value-added chemicals. The present work developed niobium oxides (Nb2O5) supported on mesoporous carbon/silica nanocomposite (MCS), as novel solid base catalyst for synthesis of HMF via one-pot glucose conversion in a biphasic solvent. The MCS material was prepared via carbonization using natural rubber dispersed in hexagonal mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…[12][13] In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis. [14][15][16][17][18][19][20][21][22][23][24][25][26] 5-hydroxymethylfurfural (HMF) is a very momentous platform compound, [27][28][29][30] HMF was obtained though the dehydration of biomass-derived carbohydrates, such as glucose, [31][32][33][34][35] fructose, [36][37][38][39][40] sucrose, [41][42][43][44][45] inulin, [46][47][48][49][50] cellobiose [51][52][53][54][55] and cellulose. [29,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13] In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis. [14][15][16][17][18][19][20][21][22][23][24][25][26] 5-hydroxymethylfurfural (HMF) is a very momentous platform compound, [27][28][29][30] HMF was obtained though the dehydration of biomass-derived carbohydrates, such as glucose, [31][32][33][34][35] fructose, [36][37][38][39][40] sucrose, [41][42][43][44][45] inulin, [46][47][48][49][50] cellobiose [51][52][53][54][55] and cellulose. [29,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%
“…In order to make full use of biomass resource, fine chemicals, and biological liquid fuel oil can be prepared by hydrogenation, oxidation, hydrolysis, esterification, reductive depolymerisationenzymatic hydrolysis, and catalytic pyrolysis [14–26] . 5‐hydroxymethylfurfural (HMF) is a very momentous platform compound, [27–30] HMF was obtained though the dehydration of biomass‐derived carbohydrates, such as glucose, [31–35] fructose, [36–40] sucrose, [41–45] inulin, [46–50] cellobiose [51–55] and cellulose [29,56–60] . Microwave technology is a simple and efficient conversion technology that can convert biomass to HMF.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, this result was attributed to an increased number of total acid sites, with especially strong acidity from 0.166 mmol/g to 0.224 mmol/g for the parent and dealuminated zeolite catalysts, respectively. Khumho et al [39] investigated the catalytic conversion of glucose into HMF over niobium oxides supported on carbon/silica nanocomposite. They found that the catalyst with the highest number of strong acid sites gave the highest yield of HMF.…”
Section: Effect Of Mild Dealumination Of H-zsm-5mentioning
confidence: 99%
“…With the increase in the consumption of fossil energy and high attention to environmental problems, the utilization of lignocellulosic biomass is believed to be an effective way to reduce energy dependence on fossil. 1 The conversion of lignocellulosic biomass into platform compounds, especially 5-hydroxymethylfurfural (5-HMF) has attracted more and more concerns since it is an important intermediate for producing a series of high-value-added products and high-quality fuels via selective oxidation, dehydration, hydroxyl aldol condensation, and hydrogenation reactions. 2 5-HMF has been widely considered an alternative to petroleum, 3,4 and expected to play a key role in chemical, fuel, medical, food fields, and so forth.…”
Section: Introductionmentioning
confidence: 99%